Comparative Effects of Alkaloid and Saponin Fractions of Rauwolfia vomitoria on Social Behaviour and Depression in a CD1 Mouse Model of Memory Impairment - Sunday A. Bisong; Favour E. Abuo; Augustine L. Udefa; Veronica E. Ironbar; Gloria B. Bassey (Archives of Current Research International, 2019)
Aqueous root bark extracts of Rauwolfia vomitoria (RV) has been reported to reduce anxiety among other uses. The study compared the effect of alkaloid and saponin fractions of RV on social behaviour and depression in scopolamine-induced memory-impaired CD1 mice. The alkaloid and saponin fractions were extracted from the root bark of the plant using standard methods. Forty-two (42) CD1 mice were grouped into six (n=7): Control mice were given placebo; three groups were given scopolamine (1.0 mg/kg, i.p.(explain) for 5 days to induce memory impairment), with 2 of them treated with the alkaloid (0.15 mg/kg, p.o.) and saponin (0.10 mg/kg, p.o.) fractions of R. vomitoria respectively. The other 2 groups were given either of the alkaloid fraction or saponin fraction of RV. Treatment lasted 21 days, after which mice were given the forced swim test and tail suspension test to assess depression and nesting test to assess social behaviour. Results showed that latency to immobility for the alkaloid fraction-treated group decreased significantly while the duration of immobility increased significantly (P<0.05) compared to control. This shows a strong positive depressive symptom. The saponin fraction-treated group however showed a significant increased in the latency to immobility while the duration of immobility decreased significantly compared to control (P<0.05). Thus, the saponin fraction of R. vomitoria decreased depression. In the test to assess social behaviour, the alkaloid group showed a significant decrease in nesting score which indicates social loss whereas the saponin group showed a significant increase (P<0.05) in nesting score compared to control. Therefore, the saponin constituent of Rauwolfia vomitoria has a high antidepressant advantage over the alkaloids fraction.